Diversity matters : - Spradlin, Lynn Kell (Wadsworth, 2012)
The book provides abundant practical, theoretically sound approaches for addressing the needs of those who are marginalized in today's classroom. Designed to engage readers intellectually and emotionally, this distinctive book will move you from the realm of understanding (head), through personal valuing (heart), and finally to applying (voice) the information provided.